Zambia - Impact Assessment of the Fertilizer Support Program : Analysis of Effectiveness and Efficiency - World Bank (World Bank, 2012)
This research report examines the technical efficiency and impact of the Zambia Fertilizer Support Program (FSP). The FSP was launched by the Government of the Republic of Zambia (GRZ) in 2002 as a temporary measure to provide subsidized hybrid maize seed and fertilizer packages to smallholder farmers and to promote the participation of private traders in supply. When the FSP was announced, the Government indicated that farmers would be eligible to receive support for two consecutive seasons only and that the subsidy level would be reduced by 25 percent per year. The program was meant to run for three years to the end of the 2004/05 farm season. Contrary to these initial plans, the scale of FSP operations has grown significantly since the program was launched with large additions to the numbers of farmers targeted in some years, a change in the subsidy level from 50 percent to 60 percent, little attention to the intended two-year "graduation" requirements, and a significant escalation of total costs and cost per beneficiary. The budgeted amount for 2007/08 was ZMK 150 billion. This assessment was prepared to help answer these questions and provide an improved basis for discussing the current and future role of agriculture input subsidies in Zambia. The request for this attests to the Zambian Government's commitment to transparent decision making. The analysis focuses specifically on the 2007/08 agriculture season.